ASSESSMENT OF THE PRACTICE OF MENTAL HYGIENE OF SECONDARY SCHOOL STUDENTS IN NSUKKA EDUCATION ZONE BASED ON LOCATION - Omeje, Chinenye B. (International Journal of Human Kinetics, Health and Education, 2023)
The study was designed to assess the practice of mental hygiene of secondary school students in Nsukka education zone based on location. In order to realize this, three research questions were raised to guide the study while hypothesis was tested at .05 level of significance. The population for the study comprised all secondary school students under Nsukka education zone in Enugu state. The multi-stage sampling technique was adopted to draw a sample size of 1,260 students for the study. Data collected was analyzed using percentages and Chi-square statistics. The result indicated that there were significant differences between urban and rural schools in their mental hygiene practices with regard to eating breakfast before going to school (X2 = 06.558 < 3.84) engaging in sport/games (X2 = 0.3816 > 3.84) and relating with teachers (X2 = 0.0436 < 3.84),. Others included going for medical treatment, (X2 = 0.0436> 3.84) overlooking annoyance (X2 = 13.7700 > 3.84) and accepting advice from people (X2 = 0.0640 > 3.84). Recommendations were made which included teachers to be encouraged to inculcate various mental hygiene practices as a means of sustaining mental health. It is necessary to prevent and avoid any form of mental illness and discomfort in the lives of the students and their teachers.